2018
DOI: 10.46903/gjms/16.03.1868
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Distribution and Determinants of Iron Deficiency Anemia Among Third Trimester Indoor Pregnant Women

Abstract: Background: Iron deficiency anemia is a common health problem during pregnancy in developing countries. The objectives of this study were to determine the frequency, distribution & determinants of iron deficiency anemia among third trimester pregnant women in our population. Materials & Methods: This cross-sectional study was conducted in Department of Gynecology and Obstetrics, Hayatabad Medical Complex, Peshawar, Pakistan from October 2015 to March 2016. Sample size was 360 calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although a few studies showed pregnancyinduced hypertension is another major factor causing 16 SGA , The mortality rate of SGA infants is higher including risk for other complications such as malnu-17 trition, delayed milestones, etc . Anemia in pregnancy is a well-researched topic in Pakistan, although many studies indicated only prevalence rates of anemic dis- [18][19] order during different trimesters of pregnancy . A researcher has defined the correlation between adverse pregnancy outcomes with the severity of anemia, mentioning SGA as one of the most commonly noted 2 complications .…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies showed pregnancyinduced hypertension is another major factor causing 16 SGA , The mortality rate of SGA infants is higher including risk for other complications such as malnu-17 trition, delayed milestones, etc . Anemia in pregnancy is a well-researched topic in Pakistan, although many studies indicated only prevalence rates of anemic dis- [18][19] order during different trimesters of pregnancy . A researcher has defined the correlation between adverse pregnancy outcomes with the severity of anemia, mentioning SGA as one of the most commonly noted 2 complications .…”
Section: Discussionmentioning
confidence: 99%